Parliamentary Procedure: Previous Question - James E. Dyer (EDIS)
The motion Previous Question is used to immediately close debate and to prevent the making of all subsidiary motions, except for the motion to Lay on the Table. Ordering the Previous Question does not prevent the making of any privileged or incidental motions, has no effect on the last question considered by the assembly, and is not allowed in committees. This 2-page fact sheet was written by James E. Dyer and published by the UF Department of Agricultural Education and Communication, January 2013.